The genus Sorastrum Kützing (Hydrodictyaceae, Sphaeropleales, Chlorophyta) from India, with a new species S. philiposianum (Bangladesh Journal of Plant Taxonomy, 2013)
In the present paper five species of Sorastrum Kützing including a new species, Sorastrum philiposianum have been described from Bankura and Purulia districts of West Bengal, India. Amongst these species S. indicum Bernard and S. hathoris (Cohn) Schmidle are being reported for the first time from India. Moreover, S. americanum (Bohlin) Schmidle is an addition to West Bengal algae. All the specimens have been collected from desmids habitats of West Bengal having a low pH (5.0-6.5) and those were growing lodged on submerged portions of the aquatic weeds like Ceratophyllum demersum L., Hydrilla verticillata (L.f.) C. Presl and Ipomoea aquatica Forssk.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17399Bangladesh J. Plant Taxon. 20(2): 243-249, 2013